Masking of Bacillus megaterium KM Membrane Reduced Nicotinamide Adenine Dinucleotide Oxidase and Solubilization Studies - Eisenberg, R. C. (1970)
Solubilization of a reduced nicotinamide adenine dinucleotide (NADH)-2,6 dichlorophenol indophenol (DCIP) oxidoreductase associated with the membrane NADH oxidase system of Bacillus megaterium KM was effected by treatment with 0.2% sodium deoxycholate, 8 m urea, or buffer (pH 9.0) in the presence of ethyl-enediaminetetraacetate. These treatments inactivated membrane NADH oxidase. It was found that membrane NADH oxidase and NADH-DCIP oxidoreductase were masked in membranes. Several procedures, including brief sonic oscillation, treatment with 0.05% deoxycholate, prolonged stirring at 4 C with 10% glycerol, and washing in the absence of Mg(2+), unmasked the oxidase and oxidoreductase activities. It was necessary to study the masking and unmasking of these activities to quantitate adequately the effects of solubilization procedures. Further information on the localization of oxidase and oxidoreductase in subcellular fractions and the effects of electron transport inhibitors on NADH oxidation was also obtained.